Effect of vitamin D3 on thyroid function and de-iodinase 2 expression in diabetic rats. (20th October 2015) - Alrefaie, Zienab; Awad, Hossam
Abstract: Objective : This study aimed to assess the effect of vitamin D3 administration to diabetic rats on thyroid profile and deiodinase 2 (D2). Methods : Thirty male Wistar rats were included into three groups; control, streptozotocin-induced diabetic and diabetic supplemented with vitamin D3 groups. Ten weeks later, serum levels of free T4, free T3 and TSH were measured. Tissue homogenates from liver, kidney, muscle, femur bone, heart and brain were obtained and assessed for D2 mRNA. Results : Diabetic rats demonstrated significant increase in free T4 and significant decrease in free T3 . These changes were ameliorated by vitamin D3 administration. D2 mRNA was significantly reduced in all tissue homogenates obtained from diabetic rats, while vitamin D3 treatment significantly enhanced D2 in liver and brain homogenates. Conclusion : Diabetes mellitus inhibited peripheral conversion of T4 into T3 secondary to reduction in D2 expression. Vitamin D3 greatly corrected the alterations in thyroid profile and D2 expression.